The effect of novel mutations on the structure and enzymatic activity of unconventional myosins associated with autosomal dominant non-syndromic hearing loss - Tae-Jun Kwon; Se-Kyung Oh; Hong-Joon Park; Osamu Sato; Hanka Venselaar; Soo Young Choi; SungHee Kim; Kyu-Yup Lee; Jinwoong Bok; Sang-Heun Lee; Gert Vriend; Mitsuo Ikebe; et al. (Open Biology, 2014)
Mutations in five unconventional myosin genes have been associated with genetic hearing loss (HL). These genes encode the motor proteins myosin IA, IIIA, VI, VIIA and XVA. To date, most mutations in myosin genes have been found in the Caucasian population. In addition, only a few functional studies have been performed on the previously reported myosin mutations. We performed screening and functional studies for mutations in the MYO1A and MYO6 genes in Korean cases of autosomal dominant non-syndromic HL. We identified four novel heterozygous mutations in MYO6. Three mutations (p.R825X, p.R991X and Q918fsX941) produce a premature truncation of the myosin VI protein. Another mutation, p.R205Q, was associated with diminished actin-activated ATPase activity and actin gliding velocity of myosin VI in an in vitro analysis. This finding is consistent with the results of protein modelling studies and corroborates the pathogenicity of this mutation in the MYO6 gene. One missense variant, p.R544W, was found in the MYO1A gene, and in silico analysis suggested that this variant has deleterious effects on protein function. This finding is consistent with the results of protein modelling studies and corroborates the pathogenic effect of this mutation in the MYO6 gene.